Future network application scenarios and network capability requirements - Linghao WANG; Miao WANG; Yawen ZHANG; Yujun ZHANG (Dianxin kexue)
The TCP/IP based internet had evolved into an important infrastructure for current information society.However,with the rapid growth of network traffic and the appearance of various emerging applications,the existing network architecture had become increasingly prominent in all aspects.Analyzing and clearing the performance needs of emerging Web applications could provide a clearer direction for the research on network architecture.The application scenarios of typical future network applications were analyzed such as immersive experience applications,IoT applications,tactile internet applications and intelligent transportation applications.The future network applications’ requirements for future networks were summarized,and key network performance indicators were derived.